Follow-up study of depressive state on patients with atrial fibrillation 1 year after radio-frequency ablation - Ren, Lei; Li, Wenjun; Su, Xin; Yang, Yangyang; Zhang, Yuanzhuo; Liu, Xiaozhu; Hu, Guangquan; Ning, Bin (Frontiers in Psychiatry, 2022)
Objective To analyze the effect of mental health status on recurrence of atrial fibrillation 1 year after radiofrequency ablation. Methods The study subjects were 91 patients with atrial fibrillation admitted to our hospital from January 2020 to July 2021. All patients were followed up 1 year after radiofrequency ablation. 91 subjects were divided into recurrence group (n=30) and no recurrence group (n=61) based on recurrence at 1 year after radiofrequency ablation. Age, course of disease, body mass index (BMI), sex, cardiac uhrasonography (left atrial diameter), inflammatory indexes in blood (neutrophil count, lymphocyte count, monocyte count) and mental health scale (MHI-5) score were compared between the two groups. Logistic multifactor regression analysis was used to analyze the influence of MHI-5 score and other indicators on recurrence of atrial fibrillation 1 year after radiofrequency ablation. Results The age of patients in the recurrence group was higher than that in the non-recurrence group (P<0.05), the course of disease was longer than that of no recurrence group (P<0.05), BMI was higher than that in the non-recurrence group (P<0.05), the left atrial diameter was larger than that of the group without recurrence (P<0.05), neutrophil count and monocyte count were significantly higher than those in non-recurrence group (P<0.05), lymphocyte count was significantly lower than that in the non-recurrence group (P<0.05). There was significant difference in the composition of MHI-5 score between the two groups (P<0.05), the composition ratio of moderate and severe depression patients in the relapse group was significantly higher than that in the non-relapse group, and the composition ratio of non-depression patients in the relapse group was significantly lower than that in the non-relapse group. Multivariate analysis showed that age, course of disease, BMI, left atrial diameter, neutrophil count, lymphocyte count, monocyte count and MHI-5 score were independent influencing factors for atrial fibrillation recurrence 1 year after radiofrequency ablation (P<0.05). Compared with non-depressed patients, patients with mild, moderate and severe depression had a 74.0%, 98.2%, 151.2% increased risk of recurrence one year after surgery (OR=1.740, 1.982, 2.512), respectively. Conclusion Depression is an important factor affecting the early recurrence of atrial fibrillation after radiofrequency ablation.